2001
DOI: 10.1002/app.10093
|View full text |Cite
|
Sign up to set email alerts
|

The characterization of organic modified clay and clay‐filled PMMA nanocomposite

Abstract: ABSTRACT:Recently, polymer-clay hybrid materials have received considerable attention from both a fundamental research and application point of view.1-3 This organicinorganic hybrid, which contains a nanoscale dispersion of the layered silicates, is a material with greatly improved physical and mechanical characteristics. These nanocomposites are synthesized through in situ polymerization or direct intercalation of the organically modified layered silicate (OLS) into the polymer matrix. Thus, understanding the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(64 citation statements)
references
References 10 publications
6
57
0
1
Order By: Relevance
“…It is well established that the glass transition (T g ) temperature either increases or decreases depending on the type of filler, its morphology and the intercrystallite distance. 42,44,58 It is also reported that the T g of PMMA depends upon the degree of tacticity (isotactic, heterotactic, syndiotactic or atactic), thermal history and the type of free radical initiator used during processing. 38,39 Since the ceramics and polymers have different heat capacities, DSC analysis is important to understand the change in the heat flow behavior due to the addition of particles into the polymer matrix.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that the glass transition (T g ) temperature either increases or decreases depending on the type of filler, its morphology and the intercrystallite distance. 42,44,58 It is also reported that the T g of PMMA depends upon the degree of tacticity (isotactic, heterotactic, syndiotactic or atactic), thermal history and the type of free radical initiator used during processing. 38,39 Since the ceramics and polymers have different heat capacities, DSC analysis is important to understand the change in the heat flow behavior due to the addition of particles into the polymer matrix.…”
Section: Resultsmentioning
confidence: 99%
“…43 In the case of clay addition into the PMMA matrix, both the thermal stability and the glass transition temperature (T g ) of the composite has been increased as compared to that of virgin polymer. 44 Significant improvement in the thermal and mechanical properties of the composites has been achieved when the graphene loading as low as 0.07% by weight mass incorporated into the PMMA matrix. 45 Similarly, alumina/PMMA composites at extremely low filler weight fractions (<1.0 wt.%), the glass-transition temperature (T g ) of composite was reduced by 25 C as compared to that of pure PMMA.…”
Section: Introductionmentioning
confidence: 99%
“…However, the molecular structure (length and number of alkyl chains and unsaturation) is also the determining factor of the thermal stability of the polymer/MMT nanocomposites. The possible mechanism for degradation of modifiers in silicates by among others Hwu et al (Hwu et al, 2002), Leszczyńska et al (Leszczyńska et al, 2007) and research has shown that surfactants degrade between 200 and 500 °C. The amount of surfactant lost during thermogravimetric analysis of various organoclays indicates that surfactants with multiple alkyl tails have greater thermal stability than those with a single alkyl tail.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…Organik ve inorganik nanokompozit malzemeler üstün özelliklerinden dolayı akademik ve endüstriyel alanda araştırmacıların dikkatini çekmekte olup hızla büyüyen bir araştırma alanıdır [1]. Nano boyuttaki inorganik maddeler organik yapılarla moleküler seviyede birleştirildiği takdirde elde edilen yapı organik-inorganik nanokompozit olarak adlandırılır [2].…”
Section: Gi̇ri̇ş (Introduction)unclassified